Perception of final year nursing students towards the Hospital Universiti Sains Malaysia (HUSM) as a clinical learning environment - Jamal, Juliana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
The clinical nursing education is one of the important components of the nursing program in preparing nurses for entry into the nursing profession. Many students reported having problems during clinical learning. Stress, anxiety and initial clinical experience are some of the problems. Therefore, attention should be given to determine factors affecting student learning outcomes in the clinical environment. There are many factors could influence students' perception toward clinical environment such as physical of the clinical area and support from staff nurses. Therefore, to get a clear view regarding this situation, the fourth year degree nursing student from University Science Malaysia (USM) and the third year diploma nursing students form Universiti Darul Nairn Malaysia (UDM) were examined by distributing survey questionnaire. It is important to explore students' perceptions about problems and conditions during clinical environment in HUSM. By understanding clinical learning experiences are essential for developing more effective clinical nursing education. This study was done to explore perceptions among final year nursing students toward Hospital Universiti Sains Malaysia (HUSM) in providing clinical learning environment. The design of this study was a cross-sectional survey using quantitative approach. The sample population was from USM and UDM. Subjects of this study were the fourth year nursing students (n=35) of University Sains Malaysia (USM) and the third year diploma students (n=28) from University Darul lman Malaysia (UDM). The potential number of student respondents from all institutions approximately n=63.